Combined Brain and Peripheral Nerve Stimulation in Chronic Stroke Patients With Moderate to Severe Motor Impairment. Issue 2 (25th October 2017) - Menezes, Isabella S.; Cohen, Leonardo G.; Mello, Eduardo A.; Machado, André G.; Peckham, Paul Hunter; Anjos, Sarah M.; Siqueira, Inara L.; Conti, Juliana; Plow, Ela B.; Conforto, Adriana B.
Abstract : Objectives: To evaluate effects of somatosensory stimulation in the form of repetitive peripheral nerve sensory stimulation (RPSS) in combination with transcranial direct current stimulation (tDCS), tDCS alone, RPSS alone, or sham RPSS + tDCS as add‐on interventions to training of wrist extension with functional electrical stimulation (FES), in chronic stroke patients with moderate to severe upper limb impairments in a crossover design. We hypothesized that the combination of RPSS and tDCS would enhance the effects of FES on active range of movement (ROM) of the paretic wrist to a greater extent than RPSS alone, tDCS alone or sham RPSS + tDCS. Materials and Methods: The primary outcome was the active ROM of extension of the paretic wrist. Secondary outcomes were ROM of wrist flexion, grasp, and pinch strength of the paretic and nonparetic upper limbs, and ROM of wrist extension of the nonparetic wrist. Outcomes were blindly evaluated before and after each intervention. Analysis of variance with repeated measures with factors "session" and "time" was performed. Results: After screening 2499 subjects, 22 were included. Data from 20 subjects were analyzed. There were significant effects of "time" for grasp force of the paretic limb and for ROM of wrist extension of the nonparetic limb, but no effects of "session" or interaction "session x time." There were no significant effects of "session, " "time, " or interaction "session x time" regarding other outcomes. Conclusions: Single sessions of PSS + tDCS, tDCS alone, or RPSS alone did not improve training effects in chronic stroke patients with moderate to severe impairment.